Prevalencia de mucositis oral en pacientes oncológicos adultos bajo radioterapia que acuden a SOLCA - LOJA en el periodo Septiembre -Diciembre 2022 - Proaño Carrillo, Gabriela Monserrath (2023)
Oral mucositis is a painful condition characterized by oral ulcers with intense pain that can cause detrimental effects during oral intake, reducing the quality of life for eating, drinking, or speaking; it usually occurs during neoplastic treatments such as radiotherapy, where we expect almost all patients to present at least some degree of oral mucositis. The purpose of this research was to determine the prevalence of oral mucositis in oncologic patients submitted to radiotherapy who attended the Solca Cancer Institute in the city of Loja and also to study the relationship between the appearance of oral mucositis with the radiation dose, the incidence of radiation cycles with the onset of mucositis and the occurrence of the pathology according to the irradiated site, through an analytical, cross-sectional study of cases and controls that we conducted with 26 patients as universe and 9 of them as a sample, we used the dental clinical history specifically elaborated for the attention of the patients of Solca Núcleo Loja and the statistical analysis was carried out with the SPSS statistical package. The results obtained were that 55.6% of the population studied presented oral mucositis, while 44.4% did not exhibit the pathology. In addition, the results showed that patients with doses of 40 GY presented initial characteristics of oral mucositis, thus concluding that radiotherapy can affect patients submitted to radiotherapy, mainly in the doses from 40 GY onwards with initial symptomatology